Problems of credit risk management in companies and means of their solution - Jasienė, Meilė; Laurinavičius, Antanas (Business: Theory and Practice, 2009)
The paper analyses credit risk management problems in non-financial companies and possible methods for reducing the risk. The research aims at determining the factors influencing the credit risk, establishes the measures reducing the risk and evaluates their effectiveness. A supplier credit is the principal short-term financing source of small and medium-size companies given the insufficient credibility and collaterals of these companies in order to obtain a credit in financial markets. Meanwhile, supplier credit means that suppliers not only finance their customers providing them with cheap resources, but also assume all the credit risk related to financing. In order to find out the ways companies assess this risk, what measures they use to manage it and the effectiveness of these measures, we carried out a research on credit risk management in building materials trading companies in Lithuania. In the course of the research, two major problems the companies confront with were identified, namely the delay of payments and losses related to so-called “bad debts”. Delays of payments may be related to limited capacities of credit managers to ensure timely recovery of debts. Long delays may also be determined by longer payment terms. This conclusion denies the attitude prevalent in practice that upon giving longer payment terms for customers, they will reduce their delays. In fact, when solving the problem of delays the companies should act in the opposite way and shorten payment terms, or deal with this problem in other ways, for example, by choosing certain measures of settlement management. Delays, in turn, directly influence the magnitude of losses related to bad debts. Therefore, in order to minimize the losses, it is necessary first of all to reduce the delays of payments. And the measures of credit risk management – as the results of the conducted research indicate – help to deal with both payment delays and losses related to bad debts. The best way to minimize delays is the use of credit insurance, suretyship and factoring because those measures involve third party into the settlement process. Thus, the „settlement discipline“, when the debtor knows that the creditor, having not received the payment in due time, may apply for the settlement to the third party, namely to the insurer, surety or factor, is created. The results of the research on credit risk management in Lithuanian building materials trading companies allow to identify the companies attributed to the lower risk group that could be held as an example to other companies and produce recommendations how to ensure a more effective risk management. Article in Lithuanian. Kredito rizikos valdymo įmonėse problemos ir jų sprendimo būdai Santrauka. Kredito rizikos valdymas nefinansinio verslo įmonėse Lietuvoje yra nauja ir menkai tyrinėta tema, ją nagrinėjančių mokslinių ir analitinių straipsnių yra nedaug. Daugiausia dėmesio, kalbant apie kredito riziką, tenka bankams, o nefinansinio verslo įmonės paliekamos nuošaly. Šių įmonių kredito rizikos analizė reikšmingai papildytų ir praturtintų kredito rizikos valdymo teoriją ir praktiką, kurios šiuo metu daugiausia sukoncentruotos į bankinės rizikos valdymą. Efektyvesnis kredito rizikos valdymas leistų sumažinti dėl pirkėjų nemokumo atsirandančius finansinius nuostolius, o kartu ir įmonės bankroto tikimybę. Straipsnyje tyrinėjamos kredito rizikos valdymo nefinansinio verslo įmonėse problemos ir galimi būdai šią riziką mažinti. Tyrimo tikslas – nustatyti kredito riziką didinančius ir mažinančius veiksnius, riziką mažinančias priemones, įvertinti jų efektyvumą; uždaviniai: apibrėžti nefinansinio verslo įmonių kredito rizikos ir jos valdymo problematiką; atlikti kredito rizikos valdymo problemų tyrimą; remiantis gautais rezultatais identifikuoti mažesnei rizikos grupei priskiriamas įmones, kurios galėtų būti pavyzdžiu kitoms; pateikti rekomendacijų, kaip užtikrinti veiksmingesnį rizikos valdymą; tyrimo objektas – Lietuvos statybinių medžiagų prekybos įmonės. Straipsnyje suformuluotos išvados ir pasiūlymai galėtų būti naudingi ir panašią veiklą plėtojančioms įmonėms. Reikšminiai žodžiai: tiekėjo kreditas, kredito rizika, atsiskaitymų vėlavimai, mokėjimo atidėjimo terminas, nuostolis. First published online: 27 Mar 2009